Legal Weak Protection of Personal Data in the 4.0 Industrial Revolution Era - Fenty Usman Puluhulawa; Jufryanto Puluhulawa; Moh. Gufran Katili (Jambura Law Review, 2020)
This study aims to discuss the legal weak protection of personal data which is motivated by the phenomenon of society today which is like living in a world without borders so that it impacts on easy access to one's personal information, the impact of begins to spread illegal practices by irresponsible parties in the illegal use of personal information. In addition, there are no laws that specifically regulate the protection of personal data/information in the 4.0 Industrial Revolution era. The approach method used is a conceptual and case approach, with the purpose of the research is to analyze the weakness of legal protection for personal data in the 4.0 Industrial Revolution era in Indonesia. The results of the study, the spread of personal data protection arrangements in various laws and regulations indicate the protection of personal data is not yet a national legal priority and results in legal weak protection of the personal data of citizens so as to position Indonesian citizens in a vulnerable position, which is certainly not in line with the legal objectives namely provide legal certainty, justice, and expediency. The various cases that exist and pay attention to the phenomenon of digitalization in the era of the industrial revolution 4.0 illustrate the urgency of the need for the legal protection of personal data a state priority. Legal reform through the legitimacy of protecting personal data as a responsive and progressive legal policy is a must so that legal protection in the form of legal guarantees can be carried out properly in order to create a safe and comfortable digital ecosystem for the community.